ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS PADA PT AGUNG BUANA REJEKI DI TANJUNG REDEB (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2017)
Financial Performance Analysis Based on Liquidity, Solvency and Profitability Ratio in PT Agung Buana Rejeki at Tanjung Redeb, the purpose of the research is to know the financial performance of PT Agung Buana Rejeki through financial statement analysis using liquidity ratio method, solvency ratio and profitability ratio. The results showed that the financial performance of PT Agung Buana Rejeki from measurement of liquidity ratio showed good results with where the company is in good condition and very able to pay off its short term debt. In the solvency ratio assessment there is an increase in debt to asset ratio of 3% and debt to equity ratio of 3% in 2015, due to the purchase of fixed assets. However, the increase is not so significant that PT Agung Buana Rejeki is able to pay off all debts if the company is liquidated. From the rationale of the profitability ratio shows that PT Agung Buana Rejeki has not been able to perform the efficiency of the costs incurred in the company this is evidenced from the decline in net profit margin from 35% in 2014 to 23% in 2015. In addition PT Agung Buana Rejeki has not been able to optimize The use of assets and capital in earning profit targeted by company management is evidenced by a decrease in ROI from 23% in 2014 to 14% in 2015, and a decrease in ROE from 25% in 2014 to 15% by 2015.